Ionic tethering contributes to the conformational stability and function of complement C3b. (May 2017) - López-Perrote, Andrés; Harrison, Reed E.S.; Subías, Marta; Alcorlo, Martín; Rodríguez de Córdoba, Santiago; Morikis, Dimitrios; Llorca, Oscar
Highlights: Ionic tethering anchors the TED domain to the macroglobulin (MG) ring of C3b. A risk polymorphism for macular degeneration disrupts ionic tethering in C3b. C3bS and C3bF variants show distinct electrostatic and conformational properties. Detachment of the TED domain is compatible with FB binding to C3b. Abstract: C3b, the central component of the alternative pathway (AP) of the complement system, coexists as a mixture of conformations in solution. These conformational changes can affect interactions with other proteins and complement regulators. Here we combine a computational model for electrostatic interactions within C3b with molecular imaging to study the conformation of C3b. The computational analysis shows that the TED domain in C3b is tethered ionically to the macroglobulin (MG) ring. Monovalent counterion concentration affects the magnitude of electrostatic forces anchoring the TED domain to the rest of the C3b molecule in a thermodynamic model. This is confirmed by observing NaCl concentration dependent conformational changes using single molecule electron microscopy (EM). We show that the displacement of the TED domain is compatible with C3b binding to Factor B (FB), suggesting that the regulation of the C3bBb convertase could be affected by conditions that promote movement in the TED domain. Our molecular model also predicts mutations that could alter the positioning of the TED domain, including the common R102G polymorphism, a risk variant for developing age-related macular degeneration. The common C3b isoform, C3bS, and the risk isoform, C3bF, show distinct energetic barriers to displacement in the TED that are related to a network of electrostatic interactions at the interface of the TED and MG-ring domains of C3b. These computational predictions agree with experimental evidence that shows differences in conformation observed in C3b isoforms purified from homozygous donors. Altogether, we reveal an ionic, reversible attachment of the TED domain to the MG ring that may influence complement regulation in some mutations and polymorphisms of C3b.